Effect of Liquid Fertilizer on Seedling Enhalus acoroides Seeds (Linnaeus f.) Royle 1839 (Fam: Hydrocharitaceae) - Chamidy, Ardian Nurrasyid; Widianingsih, Widianingsih; Munasik, Munasik; Riniatsih, Ita; Susanto, AB (Universitas Diponegoro, 2024)
The decrease in seagrass coverage and ecosystem harm to seagrass meadows is an annual occurrence resulting from both natural and human activities. Seagrass seeding has been deemed an effective restoration method, but its application is restricted by suboptimal environmental conditions and constraints associated with directly planting seagrass seeds in their natural habitat. The influence of environmental parameters, particularly nutrients, significantly affect on seagrass seed survival. NPK liquid fertilizer is commonly used in aquatic plants and is readily accessible in the market. It serves as a crucial source of macronutrients for seagrass. This study investigates the impact of different concentrations of NPK liquid fertilizer on the survival rate, growth, and chlorophyll, a content of E. acoroides seedlings. The study took place between March and May 2023 at the marine biology laboratory of the marine science study program at Diponegoro University's Faculty of Fisheries and Marine Science. According to the Manova statistical test, the NPK liquid fertilizer had an impact on the growth rate, biomass, and chlorophyll-a. The seagrass seeding container of E. acoroides treated with a liquid fertilizer concentration of 4.5 ml/100l exhibited the highest average growth rate of 0.29 cm/day and a chlorophyll-a value of 12.395 mg/g, with a survival rate of 100%. Causal connections between statements ensure logical construction. In contrast, seedlings without liquid fertilizer treatment showed the lowest growth rate of 0.19 cm/day and chlorophyll-a values of 5.169 mg/g, with a survival rate of 85.19%. Technical term abbreviations such as 'cm/day' and 'mg/g' are explained when first used to ensure clarity. Based on these findings, using liquid fertilizer with a concentration of 4.5 ml/l exhibits potential for restoring seagrass ecosystems.